Financial reforms and income inequality: Evidence from developing countries - Kwamivi Gomado (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
The current context of the COVID-19 pandemic has exposed the most vulnerable socio-economic groups to greater financial risk and thus could lead to exacerbating income inequality. The crisis creates an opportunity to demand further structural and systemic reforms for redistributive justice. Our paper explores the distributional consequences of financial liberalization reforms implemented over the past four decades in 64 emerging and low-income countries. Our identification strategy is based on a 'doubly robust' estimation approach, and impulse responses are generated by the local projection method. Our results indicate significant distributional consequences for both domestic and external finance reforms. These results are robust to alternative specifications. The results favour countries with better institutional quality. Taking the business cycle into account shows that it would be more beneficial for developing countries to implement financial reforms when the economy is growing relatively slowly. Moreover, financial reforms are effective in reducing income inequality in periods when there is no financial crisis.
Keywords: E61; D31; J48; C54; 330; financial reforms; inequality; local projection method; business cycle